Drug utilization study of drugs used in the management of post-partum hemorrhage at a tertiary care hospital - Lakshmi, G. N. S. Sangeetha; Bharathi, U.; Sruthi, Vadlakonda; Geervani, Arige (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Postpartum haemorrhage remains a major cause of both maternal mortality and morbidity worldwide, uterotonic drugs such as oxytocin, with or without ergometrine, have been used to prevent PPH. The objective to study the drugs used in the management of post-partum haemorrhage at a tertiary care hospital. Methods: An observational and cross-sectional study design was adopted for this study. The case sheets of 100 patients presenting in active stage of labour to the labour room in a tertiary care hospital were analysed. Results: In the prescriptions analysed from the patients in the labour room, drugs used to prevent PPH are oxytocin and misoprostol. Oxytocin is the most commonly prescribed drug to prevent PPH in the study group. It is a life-saving drug to prevent PPH and thereby maternal mortality. In the study group having 103 patients, a total of 81 patients received only 10 IU oxytocin IM and 14 patients received 10 IU oxytocin IM and 600 g misoprostol to prevent PPH. Conclusions: Oxytocin is an essential drug included in the WHO essential drug list and in the national list of essential medicine, so it shouldn’t have been dealt in such a biased manner.